Does climate risk undermine urban economic resilience? —Evidence from Chinese cities - Wu, Di; An, Qiguang; Zheng, Lin (Frontiers in Physics, 2025)
Climate change has become a critical global issue, influencing both natural environments and economic structures, especially in rapidly urbanizing regions. This paper examines the impact of climate risks on urban economic resilience, using panel data from Chinese cities between 2009 and 2022. A multidimensional indicator system, encompassing recovery resilience, adaptive resilience, and transformative innovation capacity, is developed to identify how climate risks negatively affect urban economic resilience. The results show that climate risks weaken resilience by reducing population size and destabilizing financial systems. Additionally, these risks have significant spatial spillover effects, extending from local areas to neighboring cities through regional economic networks, with particular impact on geographically adjacent cities. Heterogeneity analysis indicates that developed eastern cities, central cities, and resource-based cities are more vulnerable to climate risks, while cities in central and western regions and non-central cities show greater resilience. The paper proposes policy recommendations to strengthen urban resilience, including investment in climate-adaptive infrastructure, promoting economic diversification, establishing cross-regional climate risk management, developing green finance systems, and raising public awareness of climate risks.